THE HABITUAL PATTERN OF MEMORIZING SHORT SURAHS FOR CHILDREN USING THE VERSE LINKING METHOD AT THE AGE OF 4-5 YEARS IN GROUP A AT RA AL QODIR - Febri Nastiti, Laili Aulia; Akhtim Wahyuni (Academic Journal Research, 2024)
Objective: This research aims to analyze the effectiveness of the Verse-Linking Method in habituating early childhood (ages 4-5) to memorize short Quranic verses at RA Al Qodir. The study explores the planning, implementation, and evaluation stages of this method. Methods: A qualitative descriptive approach was employed, involving 25 students at RA Al Qodir. Data were collected through observations, interviews with teachers and the principal, and document analysis. The analysis process followed Miles and Huberman’s model, including data reduction, presentation, and interpretation. Results: The research identified three key stages in the memorization process: planning, implementation, and evaluation. During the planning stage, a specialized mentor guided the students, and during implementation, children engaged in a structured routine of reciting and memorizing short verses. The Verse-Linking Method proved effective in improving focus and concentration, although challenges such as inconsistent memorization times across children were noted. Evaluation involved individual assessments to confirm memorization proficiency. Novelty: The novelty of this study lies in applying the Verse-Linking Method to early childhood Quranic education, highlighting its potential to enhance memorization efficiency while fostering a conducive learning environment. This method, coupled with teacher and parent involvement, provides a comprehensive approach to Quranic education for young children.